The effects of remating interval and time of weaning on reproductive and growth fruits in New Zealand white rabbits - Chong, S.F. (2013)
Sixteen sexually mature female rabbits and their progeny were used to study the effects of remating interval and time of weaning on reproductive and growth traits in New Zealand White rabbits. The remating intervals were 1, 2, 3 and 4 weeks after birth while young rabbits were weaned at 3, 4, 5 and 6 weeks of age. Remating interval did not have a significant effect on mortality between birth and 3 weeks of age as well as between 3 and 12 weeks of age. Remating interval also did not significantly affect litter size but affected (p0.01) body weight at birth and 3 weeks of age. Remating interval, time of weaning and their interaction did not significantly affect weight at 5, 8 and 12 weeks of age.